2021
DOI: 10.1021/acs.iecr.1c04122
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fatty Acid-Based CO2-Controllable Dual-Circulation Approach for Oil Recovery

Abstract: In this article, a higher fatty acid-based ternary CO2-controllable dual-circulation had been successfully constructed, where it provided an excellent oil recovery performance and all solvents could be cycled. This dual-circulation adopted the oil-soluble higher fatty acid (HFA) as the outside loop to extract oil and selected poly­(propylene glycol) bis­(2-aminopropylether) (Jeffamine D230) as the inner loop to impel the outside loop. In washing oil technology, D230 and HFA as cleaning solvents are ideal subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…At this stage, HMF was transferred to the DES-rich phase, while the unreacted fructose was retained in the H 2 O-rich phase, and then selective separation of HMF was achieved (Figure c). More importantly, HMF can be recovered from the DES-rich phase by the addition of diethylamine (Figure d), , while DES can be easily regenerated by bubbling CO 2 because of the salting-out effect of ammonium salt generated by the reaction between CO 2 and diethylamine (Figure e) . In addition, diethylamine could be regenerated by ammonium salt through bubbling N 2 and heating and then reused in the next run. , …”
Section: Resultsmentioning
confidence: 99%
“…At this stage, HMF was transferred to the DES-rich phase, while the unreacted fructose was retained in the H 2 O-rich phase, and then selective separation of HMF was achieved (Figure c). More importantly, HMF can be recovered from the DES-rich phase by the addition of diethylamine (Figure d), , while DES can be easily regenerated by bubbling CO 2 because of the salting-out effect of ammonium salt generated by the reaction between CO 2 and diethylamine (Figure e) . In addition, diethylamine could be regenerated by ammonium salt through bubbling N 2 and heating and then reused in the next run. , …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in recent years, a new class of solvents is regulated by an intelligent solvent sensitive to external stimuli, such as pH, light, temperature, and CO 2 , to achieve reversible transformation of its physical properties, which covers the reversible change of emulsion emulsification and demulsification . If the molecules with switching characteristics are selected in the preparation design of surfactants and the appropriate ratio is studied, the use of demulsifiers can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…1), we call this an anionic SHS (ASHS). 58,65 Sed et al later reported that using a mixture of two acids, rather than a single acid, could lower the melting point and viscosity of the SHS, resulting in a wider operating temperature range and better transport properties for extraction processes (higher mass transfer coefficient, etc.). 61 An ASHS is similar in many ways to a CSHS, but the use of carboxylic acids changes the chemistry taking place.…”
Section: Introductionmentioning
confidence: 99%